2008
DOI: 10.1021/ac802332h
|View full text |Cite
|
Sign up to set email alerts
|

Sum-Frequency Spectroscopy of Molecular Adsorbates on Low-Index Ag Surfaces: Effects of Azimuthal Rotation

Abstract: Vibrational sum-frequency generation spectroscopy (SFG) lineshapes of p-cyanobenzenethiol on low-index Ag crystal surfaces are studied as a function of azimuthal rotation by angle phi. A broadband multiplex SFG method is used, with a new technique that variably suppresses the non-resonant (NR) background using time-asymmetric time-delayed picosecond laser pulses. When both resonant (R) and NR signals are present, the amplitude and phase of the R line shape can vary significantly with phi, leading to dramatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…, 24°–28° for thiophenol on Ag [27,28], and, most surprisingly, ca. 0° for MBN [29]. In view of this striking discrepancy between thiophenol and MBN on Ag, which is in sharp contrast to the findings for Au, one has to consider the reported value for Ag/MBN with caution.…”
Section: Resultsmentioning
confidence: 99%
“…, 24°–28° for thiophenol on Ag [27,28], and, most surprisingly, ca. 0° for MBN [29]. In view of this striking discrepancy between thiophenol and MBN on Ag, which is in sharp contrast to the findings for Au, one has to consider the reported value for Ag/MBN with caution.…”
Section: Resultsmentioning
confidence: 99%
“…13,45 The spectrum corresponding to high CTAC concentrations in Figure 2B is more challenging to interpret. The derivative line shape probably results from interference 46 between the C-H and water resonances. The dramatically higher contribution to the SFG signal from water relative to the C-H modes is explained by the net positive charge at the silica/aqueous interface resulting from adsorbed CTAC, which leads to a longrange array of aligned water dipoles that gives rise to a stronger resonant water signal than is observed in the low concentration spectrum (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that delaying the visible pulse results in narrower and more symmetric line shapes . In many cases, particularly when T 2 is long, the resonant signal does not decrease substantially ,, and may increase . However, in cases of rapid dephasing due to intrinsically short lifetimes, fast molecular reorientation, or energy transfer, the resonant signal will decrease with this delay.…”
mentioning
confidence: 99%
“…This increase in NR-SFG occurs along with the decrease in the resonant signal, again suggesting that more of the material is “bulk-like” rather than “interface-like”. The NR signal leads to apparent shifting of the peak positions (Figure b), but this is merely a result of the interference. , These interference effects can also lead to the creation of “ghost peaks”, such as the apparent peak at ∼3105 cm −1 , which completely disappear when the NR signal is suppressed. If the NR signal is not properly accounted for, then peak positions and amplitudes could be improperly determined, leading to erroneous physical interpretations.…”
mentioning
confidence: 99%